The covenant of water: a novel (Thorndike Press large print top shelf, ,, 2023)
"From the New York Times-bestselling author of Cutting for Stone comes a stunning and magisterial epic of love, faith, and medicine, set in Kerala, South India, following three generations of a family seeking the answers to a strange secret. The Covenant of Water is the long-awaited new novel by Abraham Verghese, the author of the major word-of-mouth bestseller Cutting for Stone, which has sold over 1.5 million copies in the United States alone and remained on the New York Times bestseller list for over two years. Spanning the years 1900 to 1977, The Covenant of Water is set in Kerala, on South India's Malabar Coast, and follows three generations of a family that suffers a peculiar affliction: in every generation, at least one person dies by drowning-and in Kerala, water is everywhere. At the turn of the century, a twelve-year-old girl from Kerala's long-existing Christian community, grieving the death of her father, is sent by boat to her wedding, where she will meet her forty-year-old husband for the first time. From this unforgettable new beginning, the young girl--and future matriarch, known as Big Ammachi--will witness unthinkable changes over the span of her extraordinary life, full of joy and triumph as well as hardship and loss, her faith and love the only constants. A shimmering evocation of a bygone India and of the passage of time itself, The Covenant of Water is a hymn to progress in medicine and to human understanding, and a humbling testament to the difficulties undergone by past generations for the sake of those alive today. Imbued with humor, deep emotion, and the essence of life, it is one of the most masterful literary novels published in recent years"--

Daisy Jones & the Six: a novel (Ballantine Books, Random House Large Print, Findaway World, LLC, Random House Publishing Group, Books on Tape, 2019)
"Daisy is a girl coming of age in L.A. in the late sixties, sneaking into clubs on the Sunset Strip, sleeping with rock stars, and dreaming of singing at the Whisky a Go-Go. The sex and drugs are thrilling, but it's the rock and roll she loves most. By the time she's twenty, her voice is getting noticed, and she has the kind of heedless beauty that makes people do crazy things. Another band getting noticed is The Six, led by the brooding Billy Dunne. On the eve of their first tour, his girlfriend Camila finds out she's pregnant, and with the pressure of impending fatherhood and fame, Billy goes a little wild on the road. Daisy and Billy cross paths when a producer realizes the key to supercharged success is to put the two together. What happens next will become the stuff of legend. The making of that legend is chronicled in this riveting and unforgettable novel, written as an oral history of one of the biggest bands of the seventies. Taylor Jenkins Reid is a talented writer who takes her work to a new level with Daisy Jones & The Six, brilliantly capturing a place and time in an utterly distinctive voice"--

After the end (G.P. Putnam's Sons, an imprint of Penguin Random House LLC, Random House Large Print, Penguin Audio, an imprint of the Penguin Random House Audio Publishing Group, Books on Tape, Penguin Publishing Group, 2019)
"Max and Pip are the strongest couple you know. They're best friends, lovers--unshakable. But then their son gets sick and the doctors put the question of his survival into their hands. For the first time, Max and Pip can't agree. They each want a different future for their son." --

To be the best (Emma Harte saga, ,, 2014)
Paula O'Neill has taken over her grandmother Emma Harte's elegant chain of department stores. Her ambition begins to override all other considerations when an opportunity to expand occurs.

The American fiancée: a novel (HarperCollins, HarperVia, an imprint of HarperCollinsPublishers, 2020)
"Born on Christmas, Louis Lamontagne, the family's patriarch, is a larger-than-life lothario and raconteur who inherits his mother's teal eyes and his father's brutish good looks and whose charms travel beyond Quebec, across the state of New York where he wins at county fairs as a larger-than-life strongman, and even in Europe, where he is deployed for the US Army during World War II. We meet his daughter, Madeleine, who opens a successful chain of diners using the recipes from her grandmother, the original American Fiancée, and vows never to return to her hometown. And we end with her son Gabriel, another ladies' man in the family, who falls in love with a woman he follows to Berlin and discovers unexpected connections there to the Lamontagne family that re-frame the entire course of the events in the book" --

Homecoming: a novel (New York Times Best Sellers Fiction, ,, 2023)
"Called home to care for her grandmother after a fall, Jess, a journalist, discovers a book chronicling the police investigation into an old unsolved murder that has a shocking connection to her family."--

Blossom Street brides (Blossom Street novel, 10,, 2015)
"Wedding bells are ringing in the community that gathers around Seattle's charming knitting shop, A Good Yarn. Lauren Elliott has waited years for her boyfriend, Todd, to propose. Knowing she can't put her future on hold, Lauren prepares to make a bold choice. Newly married to her second husband, Max, Bethanne Scranton is blissfully in love, but her cunning ex will do anything to win her back. Lydia Goetz, too, is wonderfully happy with her husband, Brad, though lately she worries about the future of A Good Yarn. Yet someone has secretly hatched a plan that brings unprecedented attention to Lydia's store. As three women's lives intersect, Lydia, Lauren, and Bethanne realize that love heals every heart, and the best surprises still lay ahead."--Cover.

This Strange Eventful History: A Novel (W.W. Norton and Company, W. W. Norton & Company, 2024)
Over seven decades, from 1940 to 2010, the pieds-noirs Cassars live in an itinerant state-separated in the chaos of World War II, running from a complicated colonial homeland, and, after Algerian independence, without a homeland at all. This Strange Eventful History, told with historical sweep, is above all a family story: of patriarch Gaston and his wife Lucienne, whose myth of perfect love sustains them and stifles their children; of Franois and Denise, devoted siblings connected by their family's strangeness; of Franois's union with Barbara, a woman so culturally different they can barely comprehend one another; of Chloe, the result of that union, who believes that telling these buried stories will bring them all peace. Inspired by stories of her own family's history, Claire Messud animates her characters' rich interior lives amidst the social and political upheaval of a recently vanished world. As profoundly intimate as it is expansive, This Strange Eventful History is "a tour de force . . . one of those rare novels which a reader doesn't merely read but lives through with the characters" (Yiyun Li).

Africaville (Amistad, an imprint of HarperCollinsPublishers, HarperCollins, Wheeler Publishing, a part of Gale, Cengage Learning, HarperAudio, Findaway World, LLC, 2019)
"Structured as a triptych, Africaville chronicles the lives of three generations of the Sebolt family--Kath Ella, her son Omar/Etienne, and her grandson Warner--whose lives unfold against the tumultuous events of the twentieth century from the Great Depression of the 1930s, through the social protests of the 1960s to the economic upheavals in the 1980s. A century earlier, Kath Ella's ancestors established a new home in Nova Scotia. Like her ancestors, Kath Ella's life is shaped by hardship--she struggles to conceive and to provide for her family during the long, bitter Canadian winters. She must also contend with the locals' lingering suspicions about the dark-skinned "outsiders" who live in their midst. Kath Ella's fierce love for her son, Omar, cannot help her overcome the racial prejudices that linger in this remote, tight-knit place. As he grows up, the rebellious Omar refutes the past and decides to break from the family, threatening to upend all that Kath Ella and her people have tried to build. Over the decades, each successive generation drifts further from Africaville, yet they take a piece of this indelible place with them as they make their way to Montreal, Vermont, and beyond, to the deep South of America. As it explores notions of identity, passing, cross-racial relationships, the importance of place, and the meaning of home, Africaville tells the larger story of the black experience in parts of Canada and the United States. Vibrant and lyrical, filled with colorful details, and told in a powerful, haunting voice, this extraordinary novel--as atmospheric and steeped in history as The Known World, Barracoon, The Underground Railroad, and The Twelve Tribes of Hattie--is a landmark work from a sure-to-be major literary talent"--

Banyan Moon: a novel (Read with Jenna, ,, 2023)
"Three Vietnamese American women mourning the death of the family matriarch recount their lives and childhoods at a crumbling, gothic manor called Banyan House, where the secrets of her grandmother's past come to light"--

Somebody's fool (Nobody's fool, 3,, 2023)
Ten years after the death of the magnetic Donald “Sully” Sullivan, the town of North Bath is going through a major transition as it is annexed by its much wealthier neighbor, Schuyler Springs. Peter, Sully’s son, is still grappling with his father’s tremendous legacy as well as his relationship to his own son, Thomas, wondering if he has been all that different a father than Sully was to him. Meanwhile, the towns’ newly consolidated police department falls into the hands of Charice Bond, after the resignation of Doug Raymer, the former North Bath police chief and Charice’s ex-lover. When a decomposing body turns up in the abandoned hotel situated between the two towns, Charice and Raymer are drawn together again and forced to address their complicated attraction to one another. Across town, Ruth, Sully’s married ex-lover, and her daughter Janey struggle to understand Janey’s daughter, Tina, and her growing obsession with Peter’s other son, Will. Amidst the turmoil, the town’s residents speculate on the identity of the unidentified body, and wonder who among their number could have disappeared unnoticed.

The poisonwood Bible: a novel (Oprah's book club, ,, 2009)
The drama of a U.S. missionary family in Africa during a war of decolonization. At its center is Nathan Price, a self-righteous Baptist minister who establishes a mission in a village in 1959 Belgian Congo. The resulting clash of cultures is seen through the eyes of his wife and his four daughters. By the author of Pigs in Heaven.

Fearless (Recorded Books, Inc., Recorded Books, Kensington Publishing Corp, Kensington Books, Clipper Audiobooks, Wheeler Publishing, a part of Gale, a Cengage Company, 2022)
Anna Campbell is ready to take her first tentative steps back into the world after widowhood. On a singles cruise, she meets divorced professor Ryan Robertson, and the sparks between them are undeniable. Back home in West Texas, Anna and Ryan continue their romance, and Anna decides it's time for their families to meet. Anna is delighted when her daughter, Christina, hits it off with Ryan's daughter, Renée. The two girls are close in age and have lots in common. Ryan's son, Patrick, is college-bound and somewhat aloof, but Anna feels sure they'll grow closer in time. She happily accepts Ryan's proposal, confident in the bond they've formed. But the idyllic relationships Anna is hoping for are quickly thrown into doubt. Ryan and his children may not be all she thinks they are. And as the situation grows more desperate, Anna must reach deep within and draw on all her courage and self-reliance to fight for the family and home she deserves ... -- provided by publisher.

A family affair (Brilliance Audio on compact disc, ,, 2017)
"In a city built on dreams, Trisha Holiday makes her living moving like one. But out of her dancer's costume, she's as down-to-earth as they come. That's why she ignores the admiring note--and the accompanying $1000 bill--that arrives backstage after one of her ethereal performances. Yet the sender, a wealthy foreign prince, isn't easily dissuaded. Seven years living and studying in the United States have made Malik long for the freedom to choose his own bride--and the woman he wants is Trisha. After a breathtaking visit to Malik's kingdom culminates in a marriage proposal, Trish attempts to adjust to an opulent new lifestyle complete with servants, sumptuous surroundings, and vast wealth. None of that matters to Trish as much as Malik's love. With Malik's sister Soraya proving a trusted new friend, they plan a lavish wedding surpassing anything she could have imagined. Yet Trish's new life will have challenges too--adjusting to a new and complex culture, to the myriad demands of Malik's royal position, and to the expectations she faces as his wife. In the midst of her own major changes, Trish vows to help her sister, Emma, whose marriage has ended in a bitter breakup. And through it all, Trish will strive to stay true to what matters most--love, true friendship, and the ties that hold family together across the miles and the years" --

Growth of the soil (Penguin classics, ,, 1921)
"The epic novel of man and nature that won its author the Nobel Prize in Literature-the first new English translation since the novel's original publication ninety years ago." --

A woman of substance (Emma Harte Saga, ,, 1987)
A dynastic novel of money and power, passion and revenge.

Quichotte: a novel (Random House, Books on Tape, Random House Audio, an imprint of the Penguin Random House Audio Publishing Group, 2019)
"Quichotte, an aging traveling salesman obsessed with the 'unreal real' of TV, falls in impossible love with a queen of the screen; while obsessively writing her love letters, he wishes an imaginary son, Sancho, into existence. Together they set off across America in Quichotte's trusty Chevy Cruze to find her and convince her of his love. Meanwhile, Quichotte's tragicomic story is being told by the author who created him: Brother, a mediocre spy novelist in the midst of a midlife crisis. As their stories intertwine, we are taken on a wild, picaresque journey through a country on the edge of moral and spiritual collapse. Just as Cervantes wrote Don Quixote to satirize the culture of his time, Rushdie brings us a new twist on a classic. Quichotte is a profoundly human love story and a wickedly entertaining satire of a corrupt age in which fact is so often indiscernible from fiction. With unforgettable characters and riveting suspense, this dazzling novel showcases an essential storyteller at his brilliant best." --

The wonder of it all (House of Falconer, 3,, 2024)
"James Falconer--a tycoon and a self-made man--seems to have the world in the palm of his hand. But the Great War looms, and James decides to fight for king and country. The fighting is bloody and brutal, and James returns a changed man, with wounds both physical and mental. His beloved wife is dead, but a new woman returns to help nurse him back to health. Georgiana Ward once held James in her thrall, but years have passed and bitterness has set in. Still, the old attraction is there and James is determined to make amends to both Georgiana and his child Leonie--now a grown woman and someone he hasn't seen in decades. Leonie is having none of it, and is embarking on a dangerous journey with a man who might very well destroy her. As James fights to return to the man he once was, he needs to find a way to heal his body, soul, and family"--

Simply sensual (Harlequin blaze, ,, 2012)
Do the job. Take the money and run. Until, in a flash, love changes everything. In retrospect, Ben Callahan should have known this job was trouble. Way more than his normal P.I. fee and unlimited expenses, just to watch over one woman and report back? Alarm bells should have sent him running back to New York. But with his Mom needing assisted living care, Ben takes Emma Montgomery's tempting offer to watch over her granddaughter. Then he meets Grace, a golden-haired princess. Gifted, gorgeous, reckless. And a serious threat to his sanity as well as his libido. Determined to prove she can support herself with her camera, Grace Montgomery hasn't touched her trust fund in months. It's a struggle, but she's free—free of stifling small-town society, free to do what she wants. And right now, she wants to explore her long-repressed sexuality with her hot new neighbor. As Grace sheds her inhibitions faster than a high-speed shutter, Ben finds himself breaking his own rules for a woman full of unexpected secrets and thousand-watt sensuality. But when Grace discovers who's signing Ben's paycheck, her heart could be too broken for his love to repair. Note: This title was originally published in 2001 by Harlequin Temptation, Blaze. It appears here in its original glory, without substantial revision.

A reunion of ghosts: a novel (Blackstone Audio, Inc, HarperCollins, HarperAudio, Harper, an imprint of HarperCollinsPublishers, Findaway World, LLC, 2015)
"In the vein of such classic family sagas as Fall on Your Knees, A Reunion of Ghosts is the confessional of three sisters who have decided to kill themselves on the very last day of the 20th century; in it they tell the story of a family haunted by suicide ever since the sisters' great-grandfather, a Nobel Prize-winning chemist, developed the first poison gas used in warfare and also the lethal agent used in the Third Reich's gas chambers--inspired in part by the troubled life of Fritz Haber, Nobel Prize winner and inventor of mustard gas"-- Three sisters have decided to kill themselves on the very last day of the 20th century. The Alter sisters-- Lady, Vee, and Delph-- are witty, complex women who share their family's apartment on Manhattan's Upper West Side. But bad luck is in their genes, passed down through the generations. As the world counts down to the dawn of a new millennium, they weave a mesmerizing account of their lives that stretches back decades to their great-grandfather, a brilliant scientist whose professional triumph became the sinister legacy that defines them.